2015
DOI: 10.14302/issn.2473-1005.jdoi-15-742
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction Of Severely Atrophic Pre-maxilla Using RhBMP-2 And Titanium Mesh For Dental Implants

Abstract: In order to achieve functional and esthetic oral rehabilitations, dental implants must be placed at an ideal tridimensional position in the alveolar bone. A clinical case is presented of a 49-year-old female with a severely resorbed pre-maxilla. Bone augmentation was conducted using the "tent pole" technique with human recombinant morphogenetic bone protein-2 embedded in an absorbable collagen sponge and deproteinized bovine bone. In addition, a titanium mesh was adapted over the graft to provide support. At 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For regenerative surgeries, many graft materials have been developed with variable properties. One relatively new material is rhBMP-2, a member of the transforming growth factor- β superfamily, which plays an important role in the modulation and differentiation of mesenchymal cells into osteoblasts [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For regenerative surgeries, many graft materials have been developed with variable properties. One relatively new material is rhBMP-2, a member of the transforming growth factor- β superfamily, which plays an important role in the modulation and differentiation of mesenchymal cells into osteoblasts [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…rhBMP-2 is the most investigated growth factor for oral and maxillofacial applications that has shown a high success rate in bone defect reconstruction [ 17 ]. In 2008, the US Food and Drug Administration approved the clinical use of rhBMP-2 in sinus lifting and localized alveolar ridge defects associated with extraction sockets [ 16 ]. Many studies have reported offlabel uses of rhBMP-2 in the reconstruction of maxillary bone defects [ 14 , 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation